2007
DOI: 10.1111/j.1745-7254.2007.00541.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telmisartan on expression of protein kinase C-? in kidneys of diabetic mice

Abstract: Aim: To investigate the effects of angiotensin receptor blocker (ARB) telmisartan on the expression and distribution of protein kinase C (PKC)-α in the kidneys of diabetic mice. Methods: Diabetic mice were induced with streptozotocin and a group of them were randomly selected for treatment with telmisartan. After 6 weeks, the expression and localization of PKC-α in the renal cortex, and the outer and inner medulla were assessed by immunohistochemistry and semiquantitative Western blotting. In addition, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 31 publications
(38 reference statements)
1
15
0
Order By: Relevance
“…Eight compounds were isolated from the chloroform layer. Compounds 4-30 were identified by detailed comparisons of their spectroscopic data with those in the literature as kaempferol (4), 13) 16) tiliroside (8), 3) quercetin (9), 17) rutin (10), 18) 24) isorhamnetin 3-O-β-d-glucopyranoside (17), 15) gallic acid (18), 25) methyl gallate (19), 26) 4-hydroxybenzoic acid (20), 27) protocatechuic acid (21), 28) methyl brevifolincarboxylate (22), 29) ursolic acid (23), 30) ursolic aldehyde (24), 31) 28-nor-urs-12-ene-3β,17β-diol (25), 32) pomolic acid (26), 33) 2α-hydroxy ursolic acid (27), 33) 23-hydroxy ursolic acid (28), 34) vomifoliol (29), 35) and β-sitosterol (30) 30) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Eight compounds were isolated from the chloroform layer. Compounds 4-30 were identified by detailed comparisons of their spectroscopic data with those in the literature as kaempferol (4), 13) 16) tiliroside (8), 3) quercetin (9), 17) rutin (10), 18) 24) isorhamnetin 3-O-β-d-glucopyranoside (17), 15) gallic acid (18), 25) methyl gallate (19), 26) 4-hydroxybenzoic acid (20), 27) protocatechuic acid (21), 28) methyl brevifolincarboxylate (22), 29) ursolic acid (23), 30) ursolic aldehyde (24), 31) 28-nor-urs-12-ene-3β,17β-diol (25), 32) pomolic acid (26), 33) 2α-hydroxy ursolic acid (27), 33) 23-hydroxy ursolic acid (28), 34) vomifoliol (29), 35) and β-sitosterol (30) 30) (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we asked whether the increase in UT-A1 phosphorylation was specific to hypertonicity or could be mimicked by directly activating PKC using a phorbol ester. Finally, we tested whether PKC-␣, a calcium-dependent PKC isoform that is expressed in the IMCD (16,22), is specifically involved in the response to hypertonicity.…”
mentioning
confidence: 99%
“…Thus, we have new insight into the beneficial mechanisms of antihypertensive agents in the treatment of renal diseases induced by oxidative stress such as diabetic nephropathy. In animal models, telmisartan has a definite renoprotective effect against renal injury in type 2 diabetic nephropathy [35,36] . In the present study, telmisartan was shown to be more effective than losartan, candesartan and olmesartan in reducing UAE, urinary 8-OHdG, and urinary L-FABP levels in early-stage diabetic nephropathy patients.…”
Section: Discussionmentioning
confidence: 99%